The goblins of English grammar - Rashid Ali, Farrah Diebaa; Nair, Mohd Azam; Gholam Hosin, Marinajan (McGraw-Hill Education (Asia), 2009)
The Goblins of English Grammar is written based on a research done on students in higher learning institutions who have difficulties with English syntax. It is practically designed for self-access learning of English syntax learners find difficult acquiring.